2017
DOI: 10.1186/s12875-017-0644-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a motivational intervention on overweight/obese patients in the primary healthcare: a cluster randomized trial

Abstract: BackgroundOverweight and obesity are common health problems which increase the risk of developing several serious health conditions. The main difficulty in the management of weight-loss lies in its maintenance, once it is achieved. The aim of this study was to investigate whether a motivational intervention, together with current clinical practice, was more efficient than a traditional intervention, in the treatment of overweight and obesity and whether this intervention reduces cardiovascular risk factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
(34 reference statements)
1
24
0
3
Order By: Relevance
“…27 In another study in primary care setting where the intervention was limited to a motivational intervention, a 5% reduction in weight was achieved by 22.6% of patients at 12 months of follow-up (no statistically significant differences with the control group) and nearly 50% of patients were lost to follow-up. 21 A possible explanation for these differences with previous studies carried out in community pharmacies or in Spanish primary care centers could be that we had no losses to follow-up while in these previous studies the average participant dropout rate ranged from 8.3% to 79%. The high retention of patients in our study could be due to this ongoing follow-up taking place when patients on regular prescription medicines collected them in the community pharmacy.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…27 In another study in primary care setting where the intervention was limited to a motivational intervention, a 5% reduction in weight was achieved by 22.6% of patients at 12 months of follow-up (no statistically significant differences with the control group) and nearly 50% of patients were lost to follow-up. 21 A possible explanation for these differences with previous studies carried out in community pharmacies or in Spanish primary care centers could be that we had no losses to follow-up while in these previous studies the average participant dropout rate ranged from 8.3% to 79%. The high retention of patients in our study could be due to this ongoing follow-up taking place when patients on regular prescription medicines collected them in the community pharmacy.…”
Section: Discussionmentioning
confidence: 68%
“…27 In another study in primary care setting where the intervention was limited to a motivational intervention, a 5% reduction in weight was achieved by 22.6% of patients at 12 months of follow-up (no statistically significant differences with the control group) and nearly 50% of patients were lost to follow-up. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main di culty in the management of weight loss lies in its maintenance once it is achieved. One study showed that signi cantly more patients in a motivational group treatment achieved a reduction of 5% or more of the initial weight and improved cardiovascular risk factors compared to the control group [24].…”
Section: Introductionmentioning
confidence: 99%